Clinical Outcomes of Double-Screw Fixation with Autologous Bone Grafting for Unstable Scaphoid Delayed or Nonunions with Cavitary Bone Loss - Ek, Eugene T.; Johnson, Paul R.; Bohan, Carmel M.; Padmasekara, Gayan (Journal of Wrist Surgery, 2020)
Objective This study reports on the clinical outcomes of double screw fixation with autologous cancellous bone grafting and early active range of motion for delayed and nonunited scaphoid waist fractures with cavitary segmental bone loss.Patients and Methods Twenty-one consecutive patients underwent fixation using two 2.2 mm antegrade headless compression screws with autologous distal radius cancellous bone graft. Postoperatively, patients were allowed early active motion with a resting splint until union was achieved. Patients were reviewed radiologically and clinically to assess for fracture union, complications, residual pain, wrist function, and return to work and recreational activities.Results All but one patient was male, and the mean age was 23 years (range, 15–38 years). The average time from initial injury was 16 months (range, 3–144 months). Nineteen of 21 (90.5%) patients achieved union at a mean of 2.8 months (range, 1.4–9.2 months). Of the patients who failed, one underwent revision surgery with vascularized bone grafting at 10.6 months. The other patient refused further intervention as he was asymptomatic.Conclusion Double-screw fixation with bone grafting and early active range of motion is a safe and effective technique for management of delayed and nonunited unstable scaphoid fractures with cavitary bone loss. This potentially allows for earlier return to function, without compromise to union rates.Level of Evidence This is a Level IV, retrospective case series study.
Keywords: scaphoid fracture; nonunion; fixation; wrist; bone graft